PENYELESAIAN WANPRESTASI ATAS PERJANJIAN KREDIT DI PT BANK BRI UNIT MUARO DENGAN NASABAH DI PENGADILAN NEGERI MUARO KELAS II (Studi Putusan Nomor 3/Pdt.G.S/2019/PN Mrj) - Muzni Karmila, Dwikornida dan (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
National development is a sustainable development effort in the context of creating a just andprosperous society based on Pancasila and the 1945 Constitution of the Republic of Indonesia.Loan agreements have been regulated and determined in Chapter Thirteen of the Third Book ofthe Civil Code, in Article 1754 of the Civil Code which clearly states that,